2013
DOI: 10.1093/scan/nst033
|View full text |Cite
|
Sign up to set email alerts
|

Neural evidence for an association between social proficiency and sensitivity to social reward

Abstract: Data from developmental psychology suggests a link between the growth of socio-emotional competences and the infant's sensitivity to the salience of social stimuli. The aim of the present study was to find evidence for this relationship in healthy adults. Thirty-five participants were recruited based on their score above the 85th or below the 15th percentile of the empathy quotient questionnaire (EQ, Baron-Cohen and Wheelwright, 2004). Functional magnetic resonance imaging (fMRI) was used to compare neural res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 63 publications
1
21
0
Order By: Relevance
“…Finally, the present study does not disentangle whether heightened empathy-related emotional responding is primarily related to the social content, the valence, or arousal aspect of the images. There has been some initial evidence showing that high empathic individuals, compared to low empathic individuals, are indeed more sensitive to cues of social versus monetary reward (Gossen et al, 2013) and that empathy-related responding is influenced by the phyologenetic similiarity of the stimuli to humans (Westbury and Neumann, 2008). A more systematic variation and experimentally testing of these variables (i.e., valence, arousal/salience aspect, and semantic content of stimuli) within one study design might be a worthwhile approach for future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the present study does not disentangle whether heightened empathy-related emotional responding is primarily related to the social content, the valence, or arousal aspect of the images. There has been some initial evidence showing that high empathic individuals, compared to low empathic individuals, are indeed more sensitive to cues of social versus monetary reward (Gossen et al, 2013) and that empathy-related responding is influenced by the phyologenetic similiarity of the stimuli to humans (Westbury and Neumann, 2008). A more systematic variation and experimentally testing of these variables (i.e., valence, arousal/salience aspect, and semantic content of stimuli) within one study design might be a worthwhile approach for future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Additional evidence suggests that the association between social preference and social behavior can be observed beyond childhood. Two cross-sectional studies of young adults found that individuals with greater sensitivity to social over nonsocial stimuli had better self-reported social functioning [5, 71]. …”
Section: Disrupted Social Preference Nmdar Hypofunction and Social mentioning
confidence: 99%
“…Variations in a key gene expressed within the human reward system (Cannabinoid Receptor gene, CNR1) were found to be associated with differences in eye-gaze fixation and neural response to happy faces (but not disgust faces) in three independent samples (Chakrabarti & Baron-Cohen, 2011;Chakrabarti, Kent, Suckling, Bullmore, & Baron-Cohen, 2006;Domschke et al, 2008). In a recent study, Gossen et al found that individuals with high trait empathy showed greater accumbens activation in response to social rewards compared to individuals with low trait empathy (Gossen et al, 2014).…”
Section: Introductionmentioning
confidence: 99%